2011
DOI: 10.1080/17452007.2011.582336
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Lean Design and Design Management and its Influence on the Development of a Multidisciplinary Design Management Model for Remote Site Projects

Abstract: A significant body of literature addresses the application of lean thinking to improving the interface between detailed design and construction production, yet none specifically focuses on remote site projects. These projects range from tourism and scientific investigation to resource exploration developments. The challenges confronting the project teams tend to fit within a sociologically oriented world where designers respond to functional, aesthetic and environmental concerns, or within a production oriente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Additionally, design management is fundamentally concerned with value generation for the customer or client, which involves the integration of various specialist knowledge and the accurate timing of critical decisions. These objectives are achieved through an integrated team approach to the design, construction, implementation, and management of a project [29].…”
Section: Design Managementmentioning
confidence: 99%
“…Additionally, design management is fundamentally concerned with value generation for the customer or client, which involves the integration of various specialist knowledge and the accurate timing of critical decisions. These objectives are achieved through an integrated team approach to the design, construction, implementation, and management of a project [29].…”
Section: Design Managementmentioning
confidence: 99%
“…However, the problems generated in the design of construction projects cannot be solved with technology alone but require an understanding of the social phenomena related to the processing of individual and collective information [9]. For this reason, certain lean tools can allow higher interactions because they encourage the management of commitment and trust among team members [10][11][12][13].Evidence exists for the application of lean management principles and some of its tools in the design management process [14,15]. For example, Fosse & Ballard [16] presented a case study that demonstrated the change between traditional planning and planning using the last planner ® system (LPS ® ) at the design phase.…”
mentioning
confidence: 99%
“…Evidence exists for the application of lean management principles and some of its tools in the design management process [14,15]. For example, Fosse & Ballard [16] presented a case study that demonstrated the change between traditional planning and planning using the last planner ® system (LPS ® ) at the design phase.…”
mentioning
confidence: 99%
“…Additionally, design management is fundamentally concerned with value generation for the customer or client, which involves integrating various specialists' knowledge and the accurate timing of critical decisions. These objectives are achieved through an integrated team approach to the design, construction, implementation, and management of a project (Kestle et al, 2011).…”
Section: Design Managementmentioning
confidence: 99%
“…Evidence exists for the application of lean management principles and some of its tools in the design management process (Kestle, Potangaroa, & Storey, 2011;Reifi & Emmitt, 2013). For example, (Fosse & Ballard, 2016) presented a case study that demonstrated the change between traditional planning and planning using the last planner® system (LPS®) at the design phase.…”
Section: 1introductionmentioning
confidence: 99%